How to Optimize the Use of Blood Cultures for the Diagnosis of Bloodstream Infections? A State-of-the Art - Lamy, Brigitte; Dargère, Sylvie; Arendrup, Maiken C.; Parienti, Jean-Jacques; Tattevin, Pierre (Frontiers in Microbiology, 2016)
Bloodstream infection (BSI) is a major cause of death in developed countries and the detection of microorganisms is essential in managing patients. Despite major progress has been made to improve identification of microorganisms, blood culture remains the gold standard and the first line tool for detecting BSIs. Consensus guidelines are available to ensure optimal BSI procedures, but blood culture practices often deviate from the recommendations. This review provides an update on clinical and technical issues related to blood collection and to blood culture performance, with a special focus on the blood sample strategy to optimize the sensitivity and specificity of blood cultures.